INTENSE PYRITE FORMATION UNDER LOW-SULFATE CONDITIONS IN THE ACHTERWASSER LAGOON, SW BALTIC SEA - Neumann T.; Rausch N.; Berner Z.; Leipe T.; Dellwig O.; Böttcher M.E. (My University, 2005)
In comparison to similar low-sulfate coastal environments with anoxic-sulfidic sediments, the Achterwasser lagoon, which is part of the Oder estuary in the SW Baltic Sea, reveals unexpectedly high pyrite concentrations of up to 7.5 wt%. Pyrite occurs mainly as framboidal grains variable in size with diameters between 1 and 20 μm. Pyritization is not uniform down to the investigated sediment depth of 50 cm. The consumption of reactive-Fe is most efficient in the upper 20 cm of the sediment column, leading to degrees of pyritization (DOP) as high as 80 to 95%.